Aptamer selection for a Trichomonas vaginalis adhesion protein 65 for diagnostic applications - Espiritu, Christian Adam L.; Rollon, Analiza P.; O'Sullivan, Ciara K. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
Trichomoniasis is the leading non-viral sexually transmitted disease worldwide. The goal of this work is to explore the potential of aptamers as the molecular recognition element in the development of diagnostic techniques for the detection of T. vaginalis infection. This work includes the selection of a single stranded DNA aptamer against a T. vaginalis adhension protein, AP65, using three different kinds of in vitro combinatorial chemistry process called systematic evolution of ligands by exponential enrichment of SELEX. After several rounds of each of the three SELEX processes, only the microtiter plate-based SELEX or p-SELEX gave a clear evolution of the library pool. One aptamer was identified following ten rounds of the p-SELEX by next generation sequencing of the enriched library pool. The high binding affinity of the aptamer to AP65 at low nM range values of the dissociation constant (Kd), was confirmed by three different techniques:surface plasmon resonance (SPR), microscale thermophoresis (MST), and, aptamer-based enzyme-linked oligonucleotide assay(ELONA). Furthermore, the ELONA showed that binding affinity of the aptamer to AP65 (Kd of 1.057nM) was better than that of the binding affinity of a polyclonal antibody using a standard indirect ELISA technique (kd of 12.47 nM). The ELONA also showed that the aptamer was specific to the AP65 protein and that it was not cross-reactive to other enteric and urogenital microorganisms.
Thesis (Ph.D. Chemical Engineering)--University of the Philippines Diliman
Keywords: Trichomonas vaginalis; Trichomoniasis; Oligonucleotides; Aptamers; Systematic evolution of ligands by exponential enrichment (SELEX).